Teacher education in computer-assisted language learning : a sociocultural and linguistic perspective - Schmid, Euline Cutrim (Advances in digital language learning and teaching, 2017)
Even though many pre-service and in-service teacher programs now address information and computer technology, computer- assisted language learning (CALL) teacher education is still reported as inadequate. Why is this? This book elaborates on some of the existing concerns and through deft analysis of longitudinal data begins to piece together a future road map for CALL teacher education.